Quality Of Life of Cancer Patients Attending a Cancer Hospital, Lumbini Province, Nepal - Panth, Asha; Gautam Bhattarai, Saraswoti Kumari; Shrestha, Durga Laxmi; K.C., Ishwori (Journal of Advanced Academic Research, 2022)
Background: Quality of life is an important aspect and high priority of the cancer patient care. The objective of the study was to find out the quality of life of cancer patients attending a Cancer hospital, Lumbini Province, Nepal. Methods: An analytical cross sectional study design based on quantitative approach was used in the study. The study was conducted in Sushil Koirala Prakhar Cancer Hospital, Khajura, Banke which was selected purposively considering only one cancer hospital in province five, Nepal. The entire cancer patients receiving at least one cycle of cancer treatment was included in the study using non probability purposive sampling technique. Semi structured interview based questionnaires was used and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire – C30 (EORTC QLQ- C30) was used for measuring quality of life. The data was collected by the enumerator by face to face interview. The collected data were analyzed by using descriptive and inferential statistics. Results: The patients with carcinoma (ca) lungs were in highest proportion (24.5%) followed by ca breast. The transform mean and SD score of Global Health/QoL was 35.84 (16.87), functional scale 36.35(15.54), symptoms scale 53.02 (14.61).Occupation was found to be associated with quality of life at statistically significant level in (p= .000) function score. Site of cancer was found to be associated with quality of life at statistically significant levels (p=.0.009) in symptom score. The patients with stage I and II had high global health score and least in stage IV. There was positive correlation of .610** (p=.000) significant at 0.01 level with functional scales and high negative correlation of -.521(p=-.521**) with symptom scales at (p=.000) level of significance. The overall quality of life of cancer patients was poor. The pain management of cancer patients should be taken into consideration.